KRITIK NALAR NIKAH MISYAR DALAM PERSPEKTIF HUKUM PERKAWINAN DI INDONESIA, ETIKA DAN MORAL - sutriyono sutriyono (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2023)
This study aims to criticize the logic of misyar marriage in the context of marriage law in Indonesia. This study uses a qualitative method with a literature review approach, which is based on Franz Magnis Suseno's critical theory about the morals and ethics of marriage in Indonesia. Misyar marriage is a form of marriage in Islamic law in which some of the rights and obligations of marriage, such as a place to live or support, are reduced or not fully implemented by the husband. The practice of misyar marriage has become a topic of debate in society because of the various views and interpretations of the law and ethics surrounding it. The critical theory approach of Franz Magnis Suseno was chosen because he is known as a philosopher who has expertise in analyzing moral and ethical issues in Indonesia. In his view, marriage is not just a legal institution, but also has an important role in shaping society's morality and ethics more broadly. Data for this study were collected through literature studies from various relevant sources, including literature on marriage law, literature on misyar marriage, views of scholars, and relevant previous research. The results of the study show that misyar marriage reaps various views in society, both those who support it and those who criticize it. Criticism of the reason for misyar marriage in the perspective of critical theory by Franz Magnis Suseno reveals several problems related to the morality and ethics of marriage. Some of them are the potential for gender inequality and women's rights, as well as the social and psychological impact on the parties involved in this kind of marriage.